Evidence for a Functional Role of the Molecular Chaperone Clusterin in Amyloidotic Cardiomyopathy - Greene, Michael J. (American Society for Investigative Pathology, 2011)
Molecular chaperones, including the extracellular protein clusterin (CLU), play a significant role in maintaining proteostasis; they have a unique capacity to bind and stabilize non-native protein conformations, prevent aggregation, and keep proteins in a soluble folding-competent state. In this study, we investigated amyloid-infiltrated cardiac tissue for the presence of CLU and measured serum levels of CLU in patients with and without amyloidotic cardiomyopathy (CMP). Cardiac tissues containing amyloid deposits composed of either transthyretin (TTR) or Ig light chain from nine patients with amyloidotic CMP were examined for the presence of CLU using immunohistochemical techniques. CLU staining coincided with the extracellular myocardial amyloid deposits in tissues from patients with familial TTR, senile systemic, and Ig light chain amyloidosis. The association of CLU with cardiac amyloid deposits was confirmed by immunogold electron microscopy. Serum concentrations of CLU were measured in familial TTR, senile systemic, and Ig light chain amyloidosis patient groups and compared with both age-matched healthy controls and with patients with CMP unrelated to amyloid disease. Subset analysis of disease cohorts, based on cardiac involvement, indicated that decreased serum CLU concentrations were associated with amyloidotic CMP. Taken together, these results suggest that CLU may play a pathogenetic role in TTR and Ig light chain amyloidoses and amyloidotic CMP.